2021
DOI: 10.3389/fgene.2021.695835
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of Single Nucleotide Polymorphisms on Fibroblast Growth Factor 19 Superfamily Genes Is Associated With Alcohol Dependence-Related Aggression

Abstract: Alcohol dependence (AD) is characterized by compulsive alcohol consumption, which involves behavioral impairments such as aggression. Members of fibroblast growth factor (FGF) 19 superfamily, including FGF19, FGF21, and FGF23, are major endocrine mediators that play an important role in alcohol metabolism and alcohol related disorders. The objective of the present study is to explore the possible associations among the interaction of single nucleotide polymorphisms (SNPs) of the FGF 19 superfamily, AD occurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…SNP analysis of Chinese patients with alcohol dependence identified a genetic interaction of specific SNPs in FGF19 and FGF21 that were predictive of high‐level alcohol dependence. The combination of these SNPs in FGF19 and FGF21 with a SNP in FGF23 was predictive of high‐level aggression and alcohol dependence (J. Xu, Wu, et al, 2021).…”
Section: Fgf Signaling In the Brain And Sensory Organsmentioning
confidence: 99%
See 1 more Smart Citation
“…SNP analysis of Chinese patients with alcohol dependence identified a genetic interaction of specific SNPs in FGF19 and FGF21 that were predictive of high‐level alcohol dependence. The combination of these SNPs in FGF19 and FGF21 with a SNP in FGF23 was predictive of high‐level aggression and alcohol dependence (J. Xu, Wu, et al, 2021).…”
Section: Fgf Signaling In the Brain And Sensory Organsmentioning
confidence: 99%
“…The combination of these SNPs in FGF19 and FGF21 with a SNP in FGF23 was predictive of high-level aggression and alcohol dependence (J. Xu, Wu, et al, 2021).…”
Section: Depressive Disordermentioning
confidence: 99%
“…The other studies confirmed the role of FGF21 SNPs in addictive behaviors like eating habits and the amount of coffee consumption ( 48 51 ). Previous studies also showed the importance of FGF21 genetic variations in obesity (rs11665896) ( 50 ), fat and macronutrient intake (rs838147) ( 51 ), renal function in diabetic patients (rs2071699, rs838136, and rs499765) ( 52 ), and alcohol dependence (rs11665896) ( 53 ) which indirectly can have effects on steatosis of liver.…”
Section: Fgf21mentioning
confidence: 94%
“…Demographic data including age and years of education were collected. Genotyping was performed as previously described ( 17 ). Briefly, genomic DNA was extracted from 5 ml peripheral blood of each participant with salting-out method, and the ZNF804A rs1344706 SNP was genotyped using MALDI-TOF based scalable MassARRAY System (Agena Bioscience, Inc., San Diego, CA, United States) with PCR primers: 5-TCAAAGCCTTATCTCTTCAC-3, 5-CCAGATAGATATCCAAGAAG-3, and single-base extension primer: 5-ACTGAAACAAAGAATCAAAAAC-3 for genotyping.…”
Section: Methodsmentioning
confidence: 99%